SCIENTIFIC PUBLICATIONS OF BRAZILIAN MASTOLOGISTS REGARDING ONCOPLASTIC AND RECONSTRUCTIVE BREAST SURGERY: A BIBLIOMETRIC STUDY - Barbosa, Gessandro Elpidio Fernandes; Pires, Douglas de Miranda; Mendonça, Ana Carolina Guglielmelli de; Valadares, Carolina Nazareth; Silva, Victor Bruno da; Nunes, Ana Maria dos Santos (Mastology, 2017)
Databases available on the Internet are important sources that enable the promotion of knowledge in the health field. Objective: To identify the scientific production of Brazilian mastologists on the subject of oncoplastic and reconstructive breast surgery published between January of 2000 and March of 2016, in the LILACS, MedLine, SciELO, PubMed and Cochrane Library databases. Methods: The identified publications were analyzed from a bibliometric perspective, and some elements such as type of publication, applied methodology, year of publication, number of job citations, Qualis ranking of the journal, number and professional profile of the authors, in addition to the publication development institution were separated and categorized. Results: A total of 631 published papers were analyzed in these databases. 76 publications were included in the final evaluation of bibliometric parameters. More than half of the evaluated publications were from the PubMed database (78.94%) and were original articles (57.89%). The average number of authors per article was 8.48. The largest number of publications included came from the year 2012 (14.47%) followed by 2013 (13.15%) and 2015 (11.84%).A significant percentage of Qualis rated journals were considered very good (A1, A2 or B1). Conclusion: The results show an evolution and an upward trend regarding the participation of Brazilian mastologist authors in national and international scientific productions related to oncoplastic and reconstructive breast surgery.